2013
DOI: 10.4049/jimmunol.1202929
|View full text |Cite
|
Sign up to set email alerts
|

Agonistic Anti-CD40 Induces Thyrocyte Proliferation and Promotes Thyroid Autoimmunity by Increasing CD40 Expression on Thyroid Epithelial Cells

Abstract: CD40 is expressed on cells of the immune system and in some tissues that are targets for autoimmune-mediated damage. It is not known if CD40 expression in target tissues plays a role in the pathology of autoimmune diseases. This study shows that agonistic anti-CD40 induces strong and sustained proliferation of thyroid epithelial cells (TEC) or thyrocytes in IFN-γ−/− autoimmune-prone NOD and NOD.H-2h4 mice. TEC proliferation is accompanied by greatly increased expression of CD40 on TEC, development of fibrosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 38 publications
(96 reference statements)
0
25
0
Order By: Relevance
“…Agonistic anti-CD40 induces proliferation of thyrocytes in IFN-γ2/2 NOD.H-2h4 mice promotes development of severe TEC H/P As mentioned above, administration of agonistic anti-CD40 to IFN-γ À/ÀCD4 À/À NOD.H-2h4 mice results in increased TEC H/P severity scores and provides a signal that enables their splenocytes to transfer severe TEC H/P to SCID recipients . During the course of these experiments, we unexpectedly observed that SCID mice, whether or not they are given donor splenocytes, have very severe thyrocyte proliferation 7 days after injection of anti-CD40 (Kayes, Fang, et al, 2013). Further studies established that thyroids of NOD and NOD.H-2h4 mice constitutively express CD40 mRNA and very low levels of CD40 protein.…”
Section: Use Of the Adoptive Transfer Model To Examine Kinetics Of Tementioning
confidence: 81%
See 4 more Smart Citations
“…Agonistic anti-CD40 induces proliferation of thyrocytes in IFN-γ2/2 NOD.H-2h4 mice promotes development of severe TEC H/P As mentioned above, administration of agonistic anti-CD40 to IFN-γ À/ÀCD4 À/À NOD.H-2h4 mice results in increased TEC H/P severity scores and provides a signal that enables their splenocytes to transfer severe TEC H/P to SCID recipients . During the course of these experiments, we unexpectedly observed that SCID mice, whether or not they are given donor splenocytes, have very severe thyrocyte proliferation 7 days after injection of anti-CD40 (Kayes, Fang, et al, 2013). Further studies established that thyroids of NOD and NOD.H-2h4 mice constitutively express CD40 mRNA and very low levels of CD40 protein.…”
Section: Use Of the Adoptive Transfer Model To Examine Kinetics Of Tementioning
confidence: 81%
“…In contrast to the relatively minimal effects of agonistic anti-CD40 on SAT development, agonistic anti-CD40 profoundly promotes development of TEC H/P and induces sustained thyrocyte proliferation in IFN-γ À/À NOD.H-2h4 mice (Section 3; Kayes, Fang, et al, 2013). NOD.H-2h4 thyrocytes also express CD40L (Kayes, Fang, et al, 2013). The effects of anti-CD40 on thyrocytes of WT and IFN-γ À/À NOD.H-2h4 mice are apparently independent of expression of CD40 ligand in the thyroid, because agonistic anti-CD40 induces the same changes in thyroids of WT and CD154À/À NOD.H-2h4 mice (our unpublished results).…”
Section: Cd40 and Cd40/cd154 Interactions In Satmentioning
confidence: 90%
See 3 more Smart Citations